PBL-based liveworksheet e-LKPD to improve critical thinking ability in 4th class primary school science learning - Triwahyudianto, Triwahyudianto; Isnani, Dewi Rahmah; Kumala, Farida Nur (Jurnal Bidang Pendidikan Dasar, 2024)
The low critical thinking ability of students in science and science learning is still not competent because learning activities still seem monotonous, teachers still do not use designing learning tools to improve critical thinking skills, especially not using interactive LKPD, therefore, researchers use PBL-based Liveworksheet software to improve critical thinking skills which aims to describe the development process, determine the level of feasibility, practicality and effectiveness of the product. This research method uses ADDIE, namely Analysis, Design, Implementation and Evaluation. Data collection techniques use test sheets and validation questionnaires on material, language, media, teacher responses and student responses. Based on these results, the PBL-based E-LKPD Liveworksheet to improve critical thinking skills is valid and practical to use for fourth grade elementary school learning activities.